The implications of cultural background on labour market choices: The case of religion and entrepreneurship - Luca Nunziata; Lorenzo Rocco (Institute for the Study of Labor (IZA), 2011)
We suggest a methodology for identifying the implications of alternative cultural and social norms embodied by religious denomination on labour market outcomes, by estimating the differential impact of Protestantism versus Catholicism on the propensity to be an entrepreneur, on the basis of the diverse minority status of both confessions across European regions. Our quasi-experimental research design exploits the stronger degree of attachment to religious ethic of religious minorities and the exogenous historical determination of the geographical distribution of religious minorities in Europe. Our analysis of European Social Survey data collected in four waves between 2002 and 2008 in 22 European countries, indicates that cultural background has a significant effect on the individual propensity to become an entrepreneur, with Protestantism increasing the chances to be an entrepreneur by around 3% with respect to Catholicism. Our findings, stable across a number of robustness checks, provide further evidence on the need to take cultural elements into consideration when analysing economic behaviour.
urn:nbn:de:101:1-201111303467
Keywords: J24; J21; Z12; Z13; 330; entrepreneurship; self-employment; religion; culture; Protestantism; Catholicism; Unternehmer; Selbstständige; Berufswahl; Religion; Wirtschaftskultur; Protestantismus; Katholizismus; Schätzung; Europa